(untitled) (Euro-Asia Conferences, 2021)
The article presents the results of studying the sorption properties of polyethylene terephthalate fiber formed from local raw materials. The dependence of the capillary-porous characteristics of the fiber on the structure of its macromolecules and the conditions of fiber formation is shown. The possibility of uniform dyeing of the fiber with dispersed scarlet in the presence of an intensifier has been established